An Arabidopsis Rhomboid homolog is an intramembrane protease in plants. - Kanaoka, M; Urban, S; Freeman, M; Okada, K (2005)
Regulated intramembrane proteolysis (RIP) is a fundamental mechanism for controlling a wide range of cellular functions. The Drosophila protein Rhomboid-1 (Rho-1) is an intramembrane serine protease that cleaves epidermal growth factor receptor (EGFR) ligands to release active growth factors. Despite differences in the primary structure of Rhomboid proteins, the proteolytic activity and substrate specificity of these enzymes has been conserved in diverse organisms. Here, we show that an Arabidopsis Rhomboid protein AtRBL2 has proteolytic activity and substrate specificity. AtRBL2 cleaved the Drosophila ligands Spitz and Keren, but not similar proteins like TGFalpha, when expressed in mammalian cells, leading to the release of soluble ligands into the medium. These studies provide the first evidence that the determinants of RIP are present in plants.